POTENSI EKSTRAK ALGA MERAH Gracilaria verrucosa SEBAGAI PENGHAMBAT PERKEMBANGAN PEMBENTUKAN BIOFILM Enterococcus faecalis PADA INFEKSI SALURAN AKAR GIGI - Putri Rahmi Noviyandri; Ridha Andayani; Ervina Rizky (Dentistry Faculty, 2018)
Enterococcus faecalis (E. faecalis) is a facultative anaerobic Gram-positive bacteria which becomesthe main bacteria occurrence failure of endodontic treatment. The red algae Gracilaria verrucosa (G. verrucosa) is one of the herbal plants that contain antibacterial compounds such as alkaloid,flavonoid, saponin, steroid, and triterpenoid. This study aims to determine the potency red algae G.verrucosa extract as inhibitor of E. faecalis biofilm formation development. The red algae G.verrucosa extract with a concentration of 100%, 75%, 25%, 12,5%, and 6,25% was made inmaceration method using ethanol 96%. Microtiter Plate Biofilm Assay method and ELISA readerwith wavelength 595nm were used to test the biofilm. The result of One Way ANOVA showedp0,05 which mean there was an effect of the test group on the formation of E. faecalis biofilm development and Post Hoc Tests-Duncan showed that there was a significant differences betweeneach group of those concentration. In the treatment group, there was found two concentration thathave significant differences, there were 100% and 6,25%. Based on the result of this study, we canconclude that the red algae G. verrucosa extract was useful as an inhibitor of E. faecalis biofilmformation development. The higher concentration of the red algae G. verrucosa, the higher its abilityas an inhibitor of E. faecalis biofilm formation development.Keywords : Enterococcus faecalis, red algae Gracilaria verrucosa, Microtiter Plate Biofilm Assaymethod, ELISA reader.